SUSCEPTIBILITY OF MICE FREE OF THEILER'S VIRUS (TO STRAIN) TO INFECTION WITH TO VIRUS - Feltz, Elmer T. (The Rockefeller University Press, 1953)
A method for the establishment and maintenance of a colony of mice free of Theiler's (TO) virus has been described. This colony has been maintained since 1947 with but one instance of contamination in 1948. Studies on the susceptibility of these mice to TO virus show that smaller doses are required to establish an infection of the intestinal tract than of the CNS. A mutant strain of TO(B) virus has been isolated which, following oral administration to mice free of TO virus, is able to cause infection of the CNS with paralysis. When fed to stock mice that carry TO virus, this TO(B) strain does not cause paralysis or other signs of CNS infection.